Kreativitas Guru dalam Meningkatkan Prestasi Belajar Peserta Didik Melalui Media Pembelajaran Pendidikan Agama Islam - Al Hamid, Ahmad (Universitas Islam Internasional Darullughah Wadda'wah, 2024)
This research aims to determine teacher creativity in improving student learning achievement through PAI learning media at Pager 2 Public Elementary School, Purwosari Pasuruan, and to determine the supporting factors and obstacles to teacher creativity in improving student learning achievement through PAI learning media at Pager 2 Purwosari Elementary School. Pasuruan. This type of research is field research with data collection techniques in the form of observation, interviews and documentation. Based on research, it is known that teachers make power point learning media and also pieces of paper with verses written on them as attractively as possible and as well as possible with colors, decorative images and sounds that can attract students' interest and overcome students' boredom in class.